Efficacy of Combined Therapy with Liposome-Encapsulated Meglumine Antimoniate and Allopurinol in Treatment of Canine Visceral Leishmaniasis - da Silva, Sydnei M. (American Society for Microbiology, 2012)
An innovative liposomal formulation of meglumine antimoniate (LMA) was recently reported to promote both long-term parasite suppression and reduction of infectivity to sand flies in dogs with visceral leishmaniasis. However, 5 months after treatment, parasites were still found in the bone marrow of all treated dogs. In order to improve treatment with LMA, the present study aimed to evaluate its efficacy in combination with allopurinol. Mongrel dogs naturally infected with Leishmania infantum were treated with six doses of LMA (6.5 mg Sb/kg of body weight/dose) given at 4-day intervals, plus allopurinol (20 mg/kg/24 h per os) for 140 days. Comparison was made with groups treated with LMA, allopurinol, empty liposomes plus allopurinol, empty liposomes, and saline. Dogs remained without treatment from day 140 to 200 after the start of treatment. The drug combination promoted both clinical improvement of dogs and significant reduction in the parasitic load in bone marrow and spleen on days 140 and 200 compared to these parameters in the pretreatment period. This is in contrast with the other protocols, which did not result in significant reduction of the bone marrow parasite load on day 200. Strikingly, the combined treatment, in contrast to the other regimens, induced negative quantitative PCR (qPCR) results in the liver of 100% of the dogs. Both xenodiagnosis and skin parasite determination by qPCR indicated that the drug combination was effective in blocking the transmission of skin parasites to sand flies. Based on all of the parasitological tests performed on day 200, 50% of the animals that received the combined treatment were considered cured.